Relative risk factors of nerve root sedimentation sign (SedSign) in patients with severe central lumbar spinal stenosis (LSS). Issue 1 (31st December 2023) - Yu, Haiming; Han, Yunfeng; Zhang, Rui; Sun, Chu; Wang, Mingda; Yue, Bo; Chou, Kaiping; Li, Bin; Zhang, Nan
Abstract : The incidence of nerve root sedimentation sign (SedSign) was evaluated to explore potential pathogenesis in patients with severe lumbar spinal stenosis (LSS). In a total of 209 patients with severe LSS, 290 intervertebral levels were narrow, among which 248 showed a positive SedSign, giving a prevalence of 85.52%. Those levels with a positive SedSign were further analyzed relative to those with a negative SedSign. There was no significant difference between the two groups for the cross-sectional area (CSA) or the posteroanterior diameter (PAD). In contrast, there was a significant difference between the groups for the grade of degenerative facet joint (DFJ) ( p  < 0.05), the thickness of ligamentum flavum (TLF) ( p  < 0.01), and the cross-sectional area difference (CSAD) ( p  < 0.01). In addition, receiver operating characteristic (ROC) curves were used to identify associated factors. The area under the ROC curve for PAD was 0.608 ( p  < 0.05), for DFJ was 0.634 ( p  < 0.05), for TLF was 0.74 ( p  < 0.01), and for CSAD was 0.911 ( p  < 0.01). In summary, a positive SedSign has notable advantages in assisting with the diagnosis of severe LSS. Compression of the dural sac from the rear may be the main risk factors of a positive SedSign.